Boosting Service Performance of Halal Restaurants: An Indonesian Experience - Aripin, Aripin; Yani, Ahmad; Jayadi, Jayadi (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This research is primarily aimed at enhancing service performance in the halal restaurant industry. It specifically investigates the role of emotional intelligence as an independent variable, and organizational citizenship behavior as a variable that serves both mediating and moderating functions. The study was conducted among 260 employees of Padang restaurants in South Jakarta, employing a quantitative approach. Data was collected through questionnaires and subsequently analyzed using path analysis with SmartPLS-3. The research reveals that emotional intelligence significantly influences service performance and that this relationship is partially mediated and moderated by organizational citizenship behavior. The findings underscore the importance of emotional intelligence and organizational citizenship behavior in enhancing service quality. Furthermore, the results reinforce the theory of dynamic capabilities (DCs), suggesting that reconfiguring internal resources, such as employees, can enhance a company’s competitive advantage in a dynamic environment. The study also offers practical implications for restaurant owners, providing insights into formulating effective strategies to improve service quality.============================================================================================================ABSTRAK - Optimalisasi Kinerja Layanan Restoran Halal: Pengalaman Indonesia. Penelitian ini bertujuan untuk menguji variabel peningkatan kinerja layanan di industri restoran halal dengan fokus pada peran kecerdasan emosional sebagai variabel independen dan organizational citizenship behavior sebagai variabel mediator sekaligus moderator. Kajian ini menggunakan pendekatan kuantitatif dimana data-data dikumpulkan melalui sebaran kuesioner kepada 260 karyawan restoran Padang di Jakarta Selatan. Hasil analisis jalur dengan SmartPLS-3 menunjukkan bahwa kecerdasan emosional berdampak signifikan terhadap kinerja layanan dan organizational citizenship behavior yang kemudian mempengaruhi kinerja layanan. Organizational citizenship behavior terbukti tidak hanya memediasi hubungan antara kecerdasan emosional dan kinerja layanan tetapi juga dapat memoderasi hubungan keduanya. Temuan ini menunjukkan pola hubungan kecerdasan emosional dalam meningkatkan kinerja layanan melalui mediasi dan moderasi organizational citizenship behavior. Studi ini menggarisbawahi pentingnya komponen kecerdasan emosional dan organizational citizenship behavior dalam meningkatkan kualitas layanan pada industri restoran halal. Kajian ini berimplikasi dalam memperkuat teori kemampuan dinamis (DCs) dimana rekonfigurasi sumber daya internal, seperti karyawan, dapat meningkatkan keunggulan kompetitif dalam lingkungan yang dinamis. Hasil ini juga memberikan implikasi praktis bagi pemilik restoran dalam merumuskan strategi yang efektif dalam meningkatkan kualitas layanan.